The truth about the Harry Quebert affair [large type] - Dicker, Joël, 1985- (Thorndike Press, 2014)
Somerset, New Hampshire, August 30, 1975: Fifteen-year-old Nola Kellergan is glimpsed fleeing through the woods, never to be heard from again. Thirty-three years later, Marcus Goldman, a successful young novelist, visits Somerset to see his mentor, Harry Quebert, one of the country's most respected writers, and to find a cure for his writer's block as his publisher's deadline looms. But Marcus's plans are violently upended when Harry is suddenly and sensationally implicated in the cold-case murder of Nola Kellergan -- whom, he admits, he had an affair with. As the national media convicts Harry, Marcus launches his own investigation, following a trail of clues through his mentor's books, the backwoods and isolated beaches of New Hampshire, and the hidden history of Somerset's citizens and the man they hold most dear. To save Harry, his own writing career, and eventually even himself, Marcus must answer three questions, all of which are mysteriously connected: Who killed Nola Kellergan? What happened one misty morning in Somerset in the summer of 1975? And how do you write a book to save someone's life?